#104 : Live Birth Rate After Preimplantation Genetic Testing for Monogenic Disorders (PGT-M) for Thalassemia in Vietnamese Patients - Lan Tram Ho; Tam Luu; Cam Tran; Nhung Nguyen; Anh Le; Tri Nguyen; Mai Ma; Vu Ho; Anh Ha; Tuong Ho (Fertility & Reproduction, 2023)
Background and Aims: Thalassemia is a hereditary blood disorder with diverse clinical manifestation inherited by autosomal recessive manner which affected 1.5% of the population. Clinically, there are two major forms: [Formula: see text]-thalassemia and [Formula: see text]-thalassemia. Palliative treatment of the severe forms by blood transfusion is eventually compromised by the concomitant problems of iron overload, alloimmunization, and bloodborne infections. In Vietnam, there are approximately 13.8% cases of thalassemia carriers in the entire population. PGT-M aims to characterize the genetic status of embryos resulting from in vitro fertilization (IVF) cycles. Herein, we report the clinical outcome of using PGT-M in couples who are thalassemia carriers. Methods: This was a case series report conducted at IVFMD, My Duc Hospital, Vietnam between April 2019 and April 2022. A total of 38 couples who underwent IVF cycle in combination with PGT-M were enrolled in this study. Trophectoderm biopsy samples undergone whole-genome amplification, followed by next-generation sequencing (NGS) via the MiSeq platform for aneuploidy screening. Specific-targeted genes were performed for thalassemia detection in the next step. Results: PGT-M was performed on a total of 128 blastocysts from 38 couples. Among 128 blastocysts, 92 (71.9%) were euploid. The rate of unaffected blastocysts was 38.0% and heterozygous blastocysts was 27.2% among euploid blastocysts. Single blastocyst transfer was performed in 30 couples and underwent 34 cycles. The clinical pregnancy rate was 50.0% and the overall live birth rate was 41.2%. Conclusion: Data from this study showed a favorable live birth rate after PGT-M for thalassemia. We should encourage carrier couples to undergo PGT-M to eliminate the transfer of this disorder through the next generation.